The effectiveness of archiving simulation video in Vocational High School - Wisnu Wibisono; Baedowi Baedowi; C. Dyah Sulistyaningrum Indrawati (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2017)
This study was a research and development. The media developed employed Ulead software with video player application. The development stage was conducted using Hannafin and Peck's development and implementation model. The instruments employed in this research were questionnaire and test. The results of interview and observation were analyzed using descriptive qualitative method, while questionnaire and test using descriptive quantitative one. Considering the result of analysis on the effectiveness of archiving simulation video using IBM SPSS 20 software with t-test formula, it could be found that the t-statistic value of posttest was 4.16 for both experiment and control classes with t-table score of 2.00; thus, tstatistic > ttable meaning that the improvement of learning outcome value for experiment class was better than that for control class. The learning outcome for experiment class showed the mean post-test score of 80.28 while that for control class of 70.56. The difference of mean posttest score between experiment and control classes was 9.72 point. The conclusion of research was that the archiving simulation video was feasible and effective to be used to improve the students' learning outcome.